The Influence Of Chemical Oxygen Demand (COD) And pH Of Pome As Biogas Raw Material On The CH4 Produced - Popi Febrianti; Dwi Kemala Putri (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
POME is liquid wastewater derived from processing of palm fruit. POME contains nitrogen, phosphate, potassium, magnesium and calcium compounds, that can be used as a good fertilizer for plantations. However, before application, POME must be processed because direct use of unprocessed POME can damage the environment. PT XYZ utilizes POME as raw material for biogas through an anaerobic fermentation process to produce alternative energy for electricity generation, however, biogas production at PT XYZ produces CH4 levels that do not meet the desired standard, namely 60%, while the value obtained is still 57%, so it can occure an incomplete combustion process in the engine. Therefore, research was carried out to analyze the influence of POME's Chemical Oygen Demand (COD) and the pH of POME as biogas raw material on the CH4 produced. Meanwhile, based on measurements of POME pH, fluctuations are caused by environmental conditions, therefore before the feed enters the biodigester, the first treatment is increasing pH until 6-7 to adjust the optimal conditions for bacteria working to break down organic substances. The results shows that the estimated potential for a Biogas Power Plant (PLTBg) with a production capacity of fresh fruit bunches (FFB) of 60 tons/hour, the high generating capacity is influenced by the large COD value, meaning that the COD value greatly influences the CH4 produced, but must also be in accordance with Other factors that influence CH4 production such as pH, temperature, stirring and others.